The Effect of Digital Media Training on Computational Thinking and Information and Communication Technology Skills of Elementary School Teachers in Kawunganten District - Nila Rozana (UM Purwokerto Press, 2025)
The rapid digital transformation has fundamentally reshaped teaching and learning processes. Today, teachers must focus not only on their existing competencies but also on mastering additional skills related to technology, critical thinking, creativity, and innovation. The Center for Curriculum Redesign (CCR) provides a robust framework for implementing 21st-century education, encompassing four essential dimensions: knowledge, skills, character, and metacognitive capabilities. Among these, computational thinking is a vital skill that supports numerous aspects of modern education. In Kawunganten District, a significant gap exists between the demand for digital competencies and the actual skills of teachers. If this challenge is not addressed immediately, we risk a decline in education quality and student skill levels, which will negatively impact human resource development in the region. It is crucial to recognize this relationship to identify and implement effective strategies for enhancing teachers' competencies in the digital era. This research employs a quantitative approach using a pre-experimental method that features a one-group pre-test and post-test design. The data analysis aims to assess the impact of digital media training on computational thinking and information and communication technology skills, ensuring that our educational strategies are both impactful and effective.